- - Figueroa Yáñez, Gonzalo (Acta Bioethica, 2000)
The author's objective is to ask himself how the "leading principles" referring to human genome have integrated in a supra national level (especially in Latin America) understanding as such the ethical values and legal regulations founded upon them. In this context, the contents of the principles of the Universal Declaration of the UNESCO concerning the human genome, acquire great importance. By warning that legal regulations can inefficiently solve some biogenetic problems, the author first addresses the concept of "human genome: mankind's common heritage". He considers that there exists a common feature in all the Conferences, Congresses and Meetings that have taken place in Latin America in relation with the issue of human genome: the demands for equal treatment -for overdeveloped and underdeveloped countries- before the benefits that new discoveries concerning the human genome would bring. The author analyses the following "leading principles": a) The principle of dignity and inviolability of the individual, throughout a strict respect for human rights. b) The principle of non- commercialization of human body. c) The principle of non- discrimination. d) The principle of confidentiality. e) The principle of free and informed consent.